A Celtic Knot. (27th September 2017) - Carter, Diane Hirabayashi
Abstract: Throughout her life Diane Hirabayashi Carter has seen a flow, or interconnection, that has led to self‐awareness. It is the awareness of the intertwining of families and life experience that can offer peace of mind and purpose.